Yemen’s crisis: international responsibility of the parties to the armed conflict - Alquhaly, Hiemyar Yahya Hamoud; Salawati Mat Basir,; Al-hameli, Bassam A. (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study offers a comprehensive analysis of the intricate legal obligations resulting from Yemen’s protracted conflict. The research examines the history of the Yemeni conflict, identifying the main players and their violations of human rights law and international humanitarian law (IHL and HRL, respectively). Using a combination of legal analysis, case studies, and a review of official reports from international bodies, the study methodically investigates specific violations, such as attacks on civilians, the use of prohibited weapons, and the obstruction of humanitarian aid. The study’s significance lies in its all-encompassing methodology in evaluating the legal obligations of state and non-state entities engaged in the war. It highlights the responsibilities these parties have under international law, particularly with regard to upholding IHL, safeguarding civilians, and ensuring war crimes are held accountable. The research draws upon primary data from victim and witness interviews, as well as original sources such as UN Security Council resolutions, Geneva Conventions, and legal precedents. The findings demonstrate that major actors, including the Saudi-led coalition, the Houthi movement, the Yemeni government, and other extremist groups, have routinely and widely violated IHL and HRL, resulting in significant civilian suffering and a humanitarian crisis. The study underscores the need for enhanced international efforts to hold violators accountable, including the use of international and national courts, and emphasizes the critical role of the UN Security Council in safeguarding civilians and promoting justice. The research contributes to the broader discourse on international legal responsibility in armed conflicts, offering critical insights and recommendations for legal and humanitarian interventions in Yemen and similar contexts.